A tale of two coalitions – marginalising the users while successfully implementing an enterprise resource planning system. (12th August 2014) - Lyytinen, Kalle; Newman, Mike
Abstract Classic analyses of system implementations view user participation as a key element for successful implementation. However, under some conditions, avoiding user participation offers an alternative route to a successful implementation; this is advisable especially when the user network is weak and aligning user needs with the technological capabilities will take too much resource. To illustrate such situation, we analyse how a successful implementation outcome of an enterprise resource planning (ERP) system emerged in a recently established conglomeration of two previously independent universities. The ERP was used to replace several legacy student administration systems for both political and functional reasons. It was deemed successful by both project consultants and the new university's management while the users were marginalised ('black boxed') and left to 'pick up the pieces' of an incomplete system using traditional methods such as shadow systems and work‐a‐rounds. Using a process approach and an actor–network theory 'reading' of related socio‐technical events, we demonstrate how three networks of actors – management, the project team and the administrative users – collided and influenced the implementation outcome and how the management and project network established the ERP as a reliable ally while at the same time the users – while being enrolled in the network – were betrayed through marginalisation. Our analysis also suggests a useful way to conduct a 'follow the network' analysis explaining and accounting for the observed implementation outcome. We illustrate the benefits of using a socio‐technical processual analysis and show how stable actor networks must be constructed during large‐scale information technology change and how different actor groups perceive and influence differently the implementation outcome.